Stosunek alimentacyjny a stosunek zobowiązaniowy - Smyczyński, Tadeusz (Wydział Prawa i Administracji UAM, 1985)
The alimentary relation and the consequent duty of alimony (a claim) is undoubtedly rooted in a model of obligation. Yet, the specificity of duty of alimony is generally noted and its intransmittability, impossibility of deduction and of renouncement are pointed out. Not all those features can decidedly distinguish the said duty from obligations regulated in the Civil Gode (CC). Contracts of supplying means for a subsistence are protected in a similar way not to deprive a creditor of his up-keep. It has to be emphasised though that the alimentary relation, contrary to legal relations regulated by the law of contracts, appeatres solely by the force of law i.e. a legal norm relates the rise of a particular obligation to a defined situation in family relations. The very alimentary relation delimits only a circle of persons who are obliged to support each other within the scope of family's solidarity. The claim for alimony on the other hand, appeares'" only in the situation when a person entitled (a creditor) is in a case of need and a person obliged (a debitor) is in a position to supply the first with means to satisfy his needs. The alimenitary relation is based on a relation of family law. Besides, there are several cases presented by the author when the duty of alimony is binding in spite of non-existence of the family law relation, i.e.: 1) between divorced spouses, (2) upon dissolution of adoption, 3) the claim of mother of an extramartial child related to pregnancy and delivery. Object of prestation is the essential distinct feature of the duty of alimony. Performance of that obligation lies in covering needs and not in the payment. Consequently, if creditor's needs are satisfied in any other way, the debtor is no longer obliged for alimony. Satisfying needs as the task of performance can also determine the debtor's behavior which consists in various actions and define the object of prestation (pecuniary, in nature). All these actions constitute the whole of prestation what results in excluding an alternative character of obligation. On the other hand, obligations regulated in the C.C. do not extinct for the reason of the creditor's living standard. It is the payment itself which is fuilfilment of prestation and an object of obligation. As it was rightly noticed in the literature, the exception of lack of impoverishment can in that case mean only a non-materialization of a concerned contractual stipulation. Relation of family law and alimentary relation in it is a type of civil law relation. The specificity of family relations which is often raised and their regulation in Family and Gardiansihip Code (F.G.C.) does not violate the qualification cited above. Another feature can be noticed though which does not differentiate a method of legal relation regulation but its task and consequent ways of solving particular family situations. For the idea is that norms of family law are to protect not that much an individual interest of particular family members, but first -of all the benefit of family group, its durability and stability.
The alimentary and the contractual relation